Anti-PD-L1 therapy altered inflammation but not survival in a lethal murine hepatitis virus-1 pneumonia model - Curran, Colleen S.; Cui, Xizhong; Li, Yan; Jeakle, Mark; Sun, Junfeng; Demirkale, Cumhur Y.; Minkove, Samuel; Hoffmann, Victoria; Dhamapurkar, Rhea; Chumbris, Symya; Bolyard, Cameron; Iheanacho, Akunna; et al. (Frontiers in Immunology, 2024)
Introduction Because prior immune checkpoint inhibitor (ICI) therapy in cancer patients presenting with COVID-19 may affect outcomes, we investigated the beta-coronavirus, murine hepatitis virus (MHV)-1, in a lethal pneumonia model in the absence (Study 1) or presence of prior programmed cell death ligand-1 (PD-L1) antibody (PD-L1mAb) treatment (Study 2). Methods In Study 1, animals were inoculated intratracheally with MHV-1 or vehicle and evaluated at day 2, 5, and 10 after infection. In Study 2, uninfected or MHV-1-infected animals were pretreated intraperitoneally with control or PD-L1-blocking antibodies (PD-L1mAb) and evaluated at day 2 and 5 after infection. Each study examined survival, physiologic and histologic parameters, viral titers, lung immunophenotypes, and mediator production. Results Study 1 results recapitulated the pathogenesis of COVID-19 and revealed increased cell surface expression of checkpoint molecules (PD-L1, PD-1), higher expression of the immune activation marker angiotensin converting enzyme (ACE), but reduced detection of the MHV-1 receptor CD66a on immune cells in the lung, liver, and spleen. In addition to reduced detection of PD-L1 on all immune cells assayed, PD-L1 blockade was associated with increased cell surface expression of PD-1 and ACE, decreased cell surface detection of CD66a, and improved oxygen saturation despite reduced blood glucose levels and increased signs of tissue hypoxia. In the lung, PD-L1mAb promoted S100A9 but inhibited ACE2 production concomitantly with pAKT activation and reduced FOXO1 levels. PD-L1mAb promoted interferon-γ but inhibited IL-5 and granulocyte-macrophage colony-stimulating factor (GM-CSF) production, contributing to reduced bronchoalveolar lavage levels of eosinophils and neutrophils. In the liver, PD-L1mAb increased viral clearance in association with increased macrophage and lymphocyte recruitment and liver injury. PD-L1mAb increased the production of virally induced mediators of injury, angiogenesis, and neuronal activity that may play role in COVID-19 and ICI-related neurotoxicity. PD-L1mAb did not affect survival in this murine model. Discussion In Study 1 and Study 2, ACE was upregulated and CD66a and ACE2 were downregulated by either MHV-1 or PD-L1mAb. CD66a is not only the MHV-1 receptor but also an identified immune checkpoint and a negative regulator of ACE. Crosstalk between CD66a and PD-L1 or ACE/ACE2 may provide insight into ICI therapies. These networks may also play role in the increased production of S100A9 and neurological mediators in response to MHV-1 and/or PD-L1mAb, which warrant further study. Overall, these findings support observational data suggesting that prior ICI treatment does not alter survival in patients presenting with COVID-19.